Corporate Governance Reporting Practices in State Owned Enterprises in South Africa - Phiri, Kada; Schutte, Danie P.; Dlamini, Banele (EuroEconomica, 2024)
Objectives: This paper analyzed corporate governance reporting practices in State Owned Enterprises (SOEs) in South Africa. Approach: The study used qualitative content analysis methodology to identify information for assessing the published annual reports of twenty-one purposively selected SOEs in South Africa. A checklist based on the corporate governance requirements of the King IV Report was used to identify the corporate governance reporting practices in SOEs. Results: The study found that most of the SOEs adhered to the King IV reporting recommendations. However, there are areas such leadership, ethics, corporate citizenship, value creation process, board evaluation and committee evaluation that detailed disclosure. Furthermore, the study found that there was inadequate guidance and oversight in terms of ethical standards and organizational culture. Implications: The study recommended that in areas where the entity has not fully complied, management should include a statement explaining the entity's commitment to comply with the required corporate governance practices and how it plans to address any weaknesses in the future. This study also recommended that the South African government should appoint board members with the necessary skills and competence to implement sound corporate governance reporting practices. Value: This research provides valuable insights into the corporate governance reporting practices of South Africa's SOEs, highlighting both adherence to and gaps in compliance with the King IV Report. It offers actionable recommendations for improving governance transparency and emphasizes the importance of skilled board appointments to strengthen oversight and ethical standards within SOEs.